Eksplorasi Terapan Refunctioned Container Menjadi Ruang-Bangunan Taman Baca Amin di Batu, Jawa Timur - Susanto, Lianggono (Institute of Research and Community Outreach - Petra Christian University, 2014)
The probelms of global warming and energy crisis have led to the birth of industrial product innovations that continues to grow, especially in the areas close to the use of fossil fuels. Combining those phenomena, one of the ideas that can be extracted from the interior and architectural designs’ point of view is Refunctioned Container building. Due to the high intensity of sun light and humidity, Indonesia is one of the countries that have started applying this idea. The objective of this paper is to describe the applied efforts of refunctioned containers at Taman Baca Amin Batu as a public library, on the basis of a qualitative research which has an explorative nature. Findings reveal that the treatments of the use of containers are different from other conventional materials, that are applied not only on the space enclosure elements; floors, walls and ceilings, but also in the material selection and use of energy (ventilation and lighting).